N-acetyl cysteine as an additive to bone cement against pathogens involved in periprosthetic joint infections - Bohn, Maja Charlotte; Oltmanns, Hilke; Harting, Heidi; Meißner, Jessica (Frontiers in Bioengineering and Biotechnology, 2025)
Periprosthetic joint infections (PJIs) and septic loosening of implants are common complications following surgical replacement of destructive joints in both human and veterinary medicine. Increasing occurrence of multi-resistant bacteria and failure to manage periprosthetic joint infections make it necessary to identify new antibacterial substances for the treatment and prevention of these infections. N-acetyl cysteine (NAC), a derivative of the amino acid cysteine, has been chosen as a candidate substance due to its shown antibacterial activity. The aim of the study was to evaluate the suitability of NAC for the use together with polymethylmethacrylate bone cement in the context of PJIs. Antibacterial activity of pure NAC and NAC-containing bone cement against clinical isolates of Staphylococcus (S.) pseudintermedius was tested by determining minimal inhibitory concentrations, analyzing growth of bacteria on bone cement, and examining the influence on infection of human osteosarcoma (HOS) cells. Cytotoxicity of pure NAC and bone cement with NAC against HOS cells was analyzed with viability and proliferation assays, Live/Dead staining of cells on bone cement, measurement of Interleukin-6 (IL-6) release, and visualizing activation of p38 MAP kinase with Western blotting. NAC inhibited growth of Staphylococcus pseudintermedius at 2.5 mg/mL and reduced bacterial growth on bone cement but could not inhibit infection of cells at 1.5 mg/mL. The IC50 of pure NAC for viability was 3.6 mg/mL. Bone cement with NAC reduced viability and proliferation at some concentrations but did not provoke IL-6 release. Western blots indicated that p38 could be activated following treatment with NAC. Taken together, antibacterial effectiveness could be shown but cytocompatibility of NAC in bone cement was limited, so that NAC cannot currently be used as a bone cement additive. Further research is necessary to balance antibacterial activity and cytotoxicity.